Distribution of chlorophyll-a concentrations in Ombai Strait Waters using aqua-modis satellite image data - Situmorang, Raymundus Putra; Gustasya, Yosy; Alamsah, Safingi; Afrisal, Muhammad; Supriyadi, Supriyadi; Sitanggang, Wanri; Ismail, Masrurah; Pramudya, Herning; Fernando, Gillang (Universitas Musamus, Merauke, Papua, 2024)
Chlorophyll-a in waters is one of the important factors that determines the primary productivity/fertility of waters. Chlorophyll-a measurements can be carried out in two ways, namely conventionally by direct measurements in the field and modernly by using remote sensing technology. The aim of this research is to determine variations in the distribution of chlorophyll-a in the waters of the Ombai Strait. The data used in this research is monthly level 3 climatology data from 2003–2022 from the Aqua-MODIS (Moderate-Resolution Imaging Spectroradiometer) satellite using a remote sensing and geographic information system approach. The results of this research were that the highest chlorophyll-a concentration was found in coastal areas and the lowest concentration was found in offshore waters. According to the monthly distribution of chlorophyll-a, the highest concentration was recorded in July with values ranging from 0.251-10.486 mg/m3 with an average of 0.566 mg/m3 and the lowest concentration was recorded in November with values ranging from 0.158-2.151 with an average of 0.427 mg/m3.